A REVIEW ON INTERNATIONAL ORGANISATIONS OF WHICH LOCAL MANAGEMENTS ARE THE MEMBER “THE SAMPLE OF METROPOLITAN MUNICIPALITY OF ANKARA” (Third Sector Social Economic Review, 2016)
Globalisation has been known as the process in which all the countries and cities affect each other with a cross-border mobility of economic, political and social structures on national, regional and local level. In this process cities and local managements come into prominence more, and so local managements, which are evaluated as the first management level for democracy and civil participation, cooperated in several networks and organisations at an international level for keeping pace with the developments on international conjuncture, being articulated with the global world and developing healthier politics. In this context, the aim of the study is to analyse the international organisations of which the local managements in Turkey are the member and their contributions to these managements specific to metropolitan municipality of Ankara.
Keywords: Local Managements; International Organisations; Metropolitan Municipality of Ankara